2021
DOI: 10.1177/15248380211036067
|View full text |Cite
|
Sign up to set email alerts
|

# Me Too: Global Progress in Tackling Continued Custodial Violence Against Women: The 10-Year Anniversary of the Bangkok Rules

Abstract: On any given day, almost 11 million people globally are deprived of their liberty. In 2020, the global female population was estimated to be 741,000, an increase of 105,000 since 2010. In order to investigate progress in the adoption of the Bangkok Rules since 2010, we conducted a legal realist assessment based on a global scoping exercise of empirical research and United Nations (UN) reporting, using detailed MESH terms across university and UN databases. We found evidences in 91 documents which directly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…Such impacts are in synergy with at least five goals directly implicated in policies for the prison system: SDG 3-Ensure healthy lives and promote well-being for all at all ages. This goal aggregates the 2010 "Bangkok Rules" and the 2015 "Nelson Mandela Rules" (11,52,53), which are existing policies to encourage changes in the field of Prison Health (54). Notably, prenatal and postnatal care and sexually transmitted diseases (STD) are highlighted.…”
Section: Considerationsmentioning
confidence: 99%
“…Such impacts are in synergy with at least five goals directly implicated in policies for the prison system: SDG 3-Ensure healthy lives and promote well-being for all at all ages. This goal aggregates the 2010 "Bangkok Rules" and the 2015 "Nelson Mandela Rules" (11,52,53), which are existing policies to encourage changes in the field of Prison Health (54). Notably, prenatal and postnatal care and sexually transmitted diseases (STD) are highlighted.…”
Section: Considerationsmentioning
confidence: 99%
“…Despite this, recent evidence reveals that 55 countries have been in violation of the Bangkok Rules (Van Hout et al, 2021). In their legal realist assessment, Van Hout and colleagues (2021) found that women in prison faced continued systemic failures to protect them from custodial violence.…”
Section: The Un Rules For the Treatment Of Prisoners And Noncustodial...mentioning
confidence: 99%
“…Despite this, recent evidence reveals that 55 countries have been in violation of the Bangkok Rules (Van Hout et al, 2021). In their legal realist assessment, Van Hout and colleagues (2021) found that women in prison faced continued systemic failures to protect them from custodial violence. They concluded that 1) the invisible nature of incarcerated women; 2) the victimization, normalization, and trivialization of violence under the guise of security; and 3) the lack of awareness and disregard of international rules hindered the full implementation of the Bangkok Rules.…”
Section: The Un Rules For the Treatment Of Prisoners And Noncustodial...mentioning
confidence: 99%
See 1 more Smart Citation
“…Women represent the minority in the global prison population and are generally detained for less severe and non-violent crimes (crimes of poverty). They are disproportionately affected by lower socioeconomic status, exposure to inter-personal violence (child abuse, intimate partner), custodial violence (prison staff, fellow prisoners) and mental illness; and often belong to identified vulnerable groups (sexual minorities, victims of sexual abuse, trafficking and drug related crime; and those with psychiatric illness, learning disabilities or drug dependence) (Karlsson and Zielinski 2020;Van Hout and Crowley 2021;Van Hout, Fleißner and Stöver 2021). Women's unique health needs in many regions of the world are often neglected by the male dominated and ill-resourced detention system.…”
Section: Introductionmentioning
confidence: 99%